A new species Cyrtodactytlus Gray (Squamata: Gekkonidae) from western Thailand and the phylogenetic placement of C. inthanon and C. doisuthep - Chomdej, Siriwadee; Suwannapoom, Chatmongkon; Pawangkhanant, Parinya; Pradit, Waranee; Nazarov, Roman A.; Grismer, L. Lee; Poyarkov, Nikolay A. (Zootaxa, 2020)
A new species of Cyrtodactylus from Tak Province, Thailand, Cyrtodactylus amphipetraeus sp. nov., is described using an integrative taxonomic analysis based on morphology, color pattern, and the mitochondrial gene NADH dehydrogenase subunit 2 (ND2). The phylogenetic analyses place the new species within the C. sinyineensis group which was previously thought to be endemic to the Salween Basin in southern Myanmar. The phylogeny also places C. inthanon in the C. sinyneensis group which is expanded herein to also include the group’s sister species C. doisuthep. Along with C. amphipetraeus sp. nov., these are the first three species of the C. sinyineensis group to be found outside of Myanmar east of the Tenasserim Mountains. The Tenasserim Mountain region is discussed as an area of cladogeneic turnover.